Hybrid poly(lactic-co-glycolic acid) nanoparticles: design and delivery prospectives. Issue 1 (January 2015) - Pandita, Deepti; Kumar, Sandeep; Lather, Viney
Highlights PLGA-hybrid nanoparticles are emerging as a versatile drug delivery vehicle. Their tunable properties and surface characteristics offer therapeutic/diagnostic solutions. PLGA–lipid nanostructures are being enormously explored.